Silicosis in Artificial Quartz Conglomerate Workers - Martínez González, Cristina; Prieto González, Amador; García Alfonso, Lucía; Fernández Fernández, Luis; Moreda Bernardo, Ariel; Fernández Álvarez, Ramon; Rolle-Sóñora, Valeria; Ruano Raviña, Alberto; Casan Clarà, Pere (Archivos de bronconeumología (English ed.), 2019)
Silicosis is a chronic progressive disease caused by inhalation of crystalline silica. Most cases develop in underground mine workers and in subjects involved in the extraction of natural stone (slate and granite). In view of the progressive emergence of new cases of silicosis in artificial quartz conglomerate workers, we performed a study to analyze the characteristics of silicosis produced by this new agent in Spain. The study consisted of a series of 96 cases of silicosis diagnosed according to international criteria during the period 2010-2017. We analyzed clinical, radiological, pathological and functional characteristics. Mean age of participants was 45 years; 55% had simple silicosis and 45% had complicated silicosis. Ten patients were diagnosed with accelerated silicosis, with a mean age of 33 years. Mean time of exposure to conglomerates was 15 years, and 77% had not used appropriate protection measures. Half of the patients were asymptomatic and presented different classic forms on chest X-ray and chest high-resolution computed tomography, along with ground-glass images. No lung function changes were recorded. Silicosis in artificial quartz conglomerate workers occurs in a young, actively employed population, a considerable percentage of whom present an accelerated form. They have few symptoms and no functional limitations. Protection measures are scarce. It is important to characterize these features to provide early diagnosis and implement the necessary preventive measures.